PENERAPAN BLUE OCEAN STRATEGY PADA UMKM SOTO KAYU BAKAR PAK MAN: Menciptakan Inovasi Nilai melalui Pengalaman Kuliner Tradisional - Ade Rifqi Husnan; Nabila Anisah Ristiana; Nabila Syakira Ramadhani; Yoiz Shofwa Shafrani (CV. Denasya Smart Publisher, 2026)
This study aims to analyze the implementation of Blue Ocean Strategy in Soto Kayu Bakar Pak Man MSMEs in creating value innovation throught and improving competitiveness in the culinary business sector. The research employed a descriptive qualitative approach using field research and library research methods. Primary data were obtained through interviews, observations, and documentation, while secondary data were collected from journals, books, and other relevant scientific sources. The results show that Soto Kayu Bakar Pak Man successfully implemented the Blue Ocean Strategy concept through product differentiation and unique consumer experiences. The use of firewood in the cooking process creates a distinctive taste and aroma that become the product’s identity and provide emotional value for consumers. In addition, affordable prices, strategic location, menu variety, as well as the use of social media and collaboration with influencers strengthen the business attractiveness. These strategies are able to create new market spaces, increase customer loyalty, and strengthen the competitive advantage of the business amid increasingly intense competition in the culinary industry